Meningkatkan Motivasi Belajar Anak Di Desa Ropoh Dengan Memanfaatkan Program Rumah Belajar - Tri Ade Setiawan; Erna Dwi Astuti; Nisfatul Munafisah (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2022)
One of the problems that exist in the community of Ropoh Village, Kepil District, Wonosobo Regency is the lack of public awareness of the importance of education. One of the programs implemented in Ropoh Village is the Learning House. The purpose of holding the Learning House program is to create public awareness of the importance of science, to create quality, character, creative and innovative human resources, to encourage and motivate children to be enthusiastic about learning and achieving achievements. The result of this Learning House program is that the children are enthusiastic in participating in these activities. In addition, the Learning House program can also help students who have difficulty in working on the practice questions given during learning activities at school.